Circular RNA-encoded oncogenic PIAS1 variant blocks immunogenic ferroptosis by modulating the balance between SUMOylation and phosphorylation of STAT1 - Xin Zang; Xiao-Yu He; Cheng-Mei Xiao; Qing Lin; Meng-Yue Wang; Cheng-Yan Liu; Ling-Yi Kong; Zhong Chen; Yuan-Zheng Xia (Molecular Cancer)
Abstract Background The clinical response rate to immune checkpoint blockade (ICB) therapy in melanoma remains low, despite its widespread use. Circular non-coding RNAs (circRNAs) are known to play a crucial role in cancer progression and may be a key factor limiting the effectiveness of ICB treatment. Methods The circRNAs that were downregulated after coadministration compared with single administration of PD-1 inhibitor administration were identified through RNA-seq and Ribo-seq, and thus the circPIAS1 (mmu_circ_0015773 in mouse, has_circ_0008378 in human) with high protein coding potential was revealed. Fluorescence in situ hybridization (FISH) assays were conducted to determine the localization of circPIAS1 in human and mouse melanoma cells, as well as its presence in tumor and adjacent tissues of patients. Validation through dual-luciferase reporter assay and LC–MS/MS confirmed the ability of circPIAS1 to encode a novel 108 amino acid polypeptide (circPIAS1-108aa). Specific antisense oligonucleotides (ASOs) targeting the junction site of circPIAS1 were developed to reduce its intracellular levels. Proliferation changes in melanoma cells were assessed using CCK8, EdU, and colony formation assays. The impact of circPIAS1-108aa on the ferroptosis process of melanoma cells was studied through GSH, MDA, and C11-BODIPY staining assays. Western Blot, Immunoprecipitation (IP), and Immunoprecipitation-Mass Spectrometry (IP-MS) techniques were employed to investigate the impact of circPIAS1-108aa on the P-STAT1/SLC7A11/GPX4 signaling pathway, as well as its influence on the balance between STAT1 SUMOylation and phosphorylation. Additionally, a melanoma subcutaneous transplanted tumor mouse model was utilized to examine the combined effect of reducing circPIAS1 levels alongside PD-1 inhibitor. Results Compared with the group treated with PD-1 inhibitor alone, circPIAS1 was significantly down-regulated in the coadministration group and demonstrated higher protein coding potential. CircPIAS1, primarily localized in the nucleus, was notably upregulated in tumor tissues compared to adjacent tissues, where it plays a crucial role in promoting cancer cell proliferation. This circRNA can encode a unique polypeptide consisting of 108 amino acids, through which it exerts its cancer-promoting function and impedes the effectiveness of ICB therapy. Mechanistically, circPIAS1-108aa hinders STAT1 phosphorylation by recruiting SUMO E3 ligase Ranbp2 to enhance STAT1 SUMOylation, thereby reactivating the transduction of the SLC7A11/GPX4 signaling pathway and restricting the immunogenic ferroptosis induced by IFNγ. Furthermore, the combination of ASO-circPIAS1 with PD-1 inhibitor effectively inhibits melanoma growth and significantly enhances the efficacy of immune drugs in vivo. Conclusions Our study uncovers a novel mechanism regarding immune evasion in melanoma driven by a unique 108aa peptide encoded by circPIAS1 in melanoma that dramatically hinders immunogenic ferroptosis triggered by ICB therapy via modulating the balance between SUMOylation and phosphorylation of STAT1. This work reveals circPIAS1-108aa as a critical factor limiting the immunotherapeutic effects in melanoma and propose a promising strategy for improving ICB treatment outcomes.